A Review of Embodied Energy Strategies to reduce the carbon emissions in Sustainable Buildings - Baishali Pradhan; Bandana Jha (International Journal of Architectural Design and Planning, 2025)
Buildings in India account for almost one-fifth of the nation's carbon emissions, making it the third- largest carbon emitter globally. These emissions are expected to climb by 50% over the next 20 years, which is the biggest increase of any nation. You would have to go into a jungle to avoid concrete, steel, and aluminium since they are so common. Just these three substances are responsible for 23% of the world's carbon emissions. They are widely employed in modern buildings and infrastructures. To achieve our climate targets, we must cut and eliminate emissions connected with these materials. Buildings account for roughly 40% of annual carbon emissions, with 12% coming from embodied carbon and 28% from operational carbon. Construction materials are extracted, processed, and manufactured before being delivered to the site and combined to form the building. These emissions are expected to climb by 50% over the next two decades, the most of any country. During this period, India's built floor space is predicted to more than double, resulting in a large need for building materials. Cement consumption will more than treble, steel demand will nearly quadruple, and brick demand will rise three to fourfold. Buildings have long lifespans, so the effects of embodied carbon are locked in for decades. The International Energy Agency believes that currently available alternative materials might lower world cumulative emissions by 70%. This study investigates techniques for lowering CO2 emissions by addressing embodied energy in sustainable buildings. This study examines the impact of embodied energy in the building, materials specification, lifecycle energy analysis using embodied energy, and solutions for optimizing embodied energy from buildings.
Keywords: CO2 emissions; Embodied energy; LCEA; Materials; Sustainable Buildings